2012
DOI: 10.2174/157340012803520414
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Addiction: Past, Present and Future

Abstract: Abstract:Gaming addiction has become a topic of increasing research interest. The last decade has witnessed a significant increase in the number of empirical studies examining various aspects of problematic video game play and video game addiction. This paper begins with a brief past history of how research into video game addiction has changed over the last three decades (i.e., the 1980s, 1990s and 2000s). It then examines more thoroughly the contemporary research literature by analyzing the (i) prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
157
1
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(190 citation statements)
references
References 101 publications
7
157
1
11
Order By: Relevance
“…This line of research has been far from systematic (Salguero & Morán, 2002), and despite the increase of epidemiological studies over the last decade there is still insufficient empirical research to support the notion that VGA could be classed as a psychiatric disorder (King et al, 2013a), although the empirical research is rapidly 4 4 growing (Griffiths, Kuss, & King, 2012). From the mid-1990s to the present day, the prevalence of VGA among various populations has differed widely.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research has been far from systematic (Salguero & Morán, 2002), and despite the increase of epidemiological studies over the last decade there is still insufficient empirical research to support the notion that VGA could be classed as a psychiatric disorder (King et al, 2013a), although the empirical research is rapidly 4 4 growing (Griffiths, Kuss, & King, 2012). From the mid-1990s to the present day, the prevalence of VGA among various populations has differed widely.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers consider video games as the starting point for examining the characteristics of gaming disorder [10,18], while others consider the internet as the main platform that unites different addictive internet activities, including online games [19,20]. For instance, Griffiths [21] has argued that although all addictions have particular and idiosyncratic characteristics, they share more commonalities than differences (i.e., salience, mood modification, tolerance, withdrawal symptoms, conflict, and relapse), and likely reflect a common etiology of addictive behavior.…”
mentioning
confidence: 99%
“…Although there is now a rapidly growing body of literature on gaming addiction (Griffiths, Kuss, & King, 2012), one of the key reasons that IGD was not included in the main text of the DSM-5 was that the SUDWG concluded that standard diagnostic criteria were not used to assess gaming addiction across these many studies.…”
Section: Internet Addiction: the Debatesmentioning
confidence: 99%